Pemanfaatan Sistem Informasi Edukasi Mitigasi Bencana pada KSR PMI Unit Markas Majene - Nahya Nur; Farid Wajidi; Ade Mulawarman; Muh. Adrian; Rifky Gunawan (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2022)
The availability of information related to disasters is one of the efforts so that the public better understands the actions that must be taken to minimize the risks that occur. However, the availability of this information, especially in the Majene Regency area, is currently still quite minimal. In fact, Majene is one of the areas with a fairly high Disaster Risk Index. This activity embraces the Voluntary Corps (KSR) PMI Majene Headquarters Unit as a partner considering that KSR is one of the organizations engaged in the humanitarian field and actively participates in disaster management. The activities carried out include the use of a disaster education information system by providing training to KSR members in managing the system and creating disaster education content. The results of the activities obtained show an increase in the ability of KSR members in terms of management and content creation using Canva and hopes that the disaster education information system that has been built can continue to be used for the dissemination of disaster information.